Analisis Kesiapan Kerja Lulusan Sekolah Menengah Kejuruan Jurusan Teknik Instalasi Tenaga Listrik - Sukma Angraini Nauli Harahap; Oriza Candra (Jurnal Pendidikan Teknik Elektro, 2023)
This research aims to analyze the job readiness of Electrical Power Installation Engineering department graduates at SMK Negeri 3 Sibolga. Work readiness is the overall condition of an individual which includes physical, and mental life, and experiences that encourage a person to be willing to work together with other people, be critical, accept responsibility, and have the ambition to progress and be able to adapt to the work environment. The research method used in this research is a descriptive research method with a quantitative approach. The variable studied was the work readiness of graduates majoring in Electrical Power Installation Engineering at SMK Negeri 3 Sibolga. The research instrument used in this research was a questionnaire which was distributed to respondents online using a Google form which had 1 variable and 7 indicators. This research questionnaire was conducted on graduates of the 2022/2023 academic year in Electrical Power Installation Engineering, totaling 31 respondents, and obtained results of 48% who have good work readiness. The results of this research can conclude that the work readiness of graduates for the 2022/2023 academic year, majoring in Electrical Power Installation Engineering at SMK Negeri 3 Sibolga is categorized as good.